2014
DOI: 10.1111/jcpp.12214
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Two pathways toward impulsive action: an integrative risk model for bulimic behavior in youth

Abstract: Background This paper provides an integrative review of existing risk factors and models for bulimia nervosa (BN) in young girls. We offer a new model for BN that describes two pathways of risk that may lead to the initial impulsive act of binge eating and purging in children and adolescents. Scope We conducted a selective literature review, focusing on existing and new risk processes for BN in this select population. Findings We identify two ways in which girls increase their risk to begin engaging in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 98 publications
(159 reference statements)
1
32
0
1
Order By: Relevance
“…The greater harms reported by women with eating disorders may partly be caused by increased sensitivity to the harmful effects of drinking, perhaps because of food deprivation or purging‐related fluid and electrolyte imbalances. Personality traits such as impulsivity or novelty seeking that are associated with both substance use and bulimic behaviors, may also contribute the association, or drinking may be a strategy to reduce anxiety Further, eating disorders and risky drinking may have a shared etiology . Indeed, classical twin studies have demonstrated that alcohol use disorders and eating disorders share familial and genetic liability .…”
Section: Discussionmentioning
confidence: 99%
“…The greater harms reported by women with eating disorders may partly be caused by increased sensitivity to the harmful effects of drinking, perhaps because of food deprivation or purging‐related fluid and electrolyte imbalances. Personality traits such as impulsivity or novelty seeking that are associated with both substance use and bulimic behaviors, may also contribute the association, or drinking may be a strategy to reduce anxiety Further, eating disorders and risky drinking may have a shared etiology . Indeed, classical twin studies have demonstrated that alcohol use disorders and eating disorders share familial and genetic liability .…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have repeatedly demonstrated high rates of mood and anxiety disorders (Dani & Harris, 2005; Grant et al, 2004; Hasin et al, 2007; Hudson et al, 2007; Kessler et al, 2013) among EDs and SUDs and, like other psychiatric disorders and SUDs, are influenced by genetic factors (Shimada-Sugimoto, Otowa, & Hettema, 2015; Sullivan, Neale, & Kendler, 2000); thus, the inclusion of these disorders will be an important part of our overall understanding of shared genetic risk for ED-SUD comorbidity. Similarly, given literature stating that there may be an addictive personality underlying this comorbidity (Holderness et al, 1994), which is marked by impulsivity and novelty seeking that are common in EDs and SUDs (Dick et al, 2010; Pearson, Riley, Davis, & Smith, 2014), it will be important to investigate how personality features that are themselves influenced by genetic factors (Bouchard & Loehlin, 2001) impact the ED and SUD association. Taken together, once more information is obtained about how other psychopathology and personality traits influence genetic effects on ED-SUD comorbidity from a more basic level and in the context of environmental factors, the novel statistical techniques discussed above (e.g., PRS) can be combined with environmental risk factors to provide important clues into who may be at highest risk for the development of EDs, SUDs, and their comorbidity.…”
Section: Avenues For Future Researchmentioning
confidence: 99%
“…Notably, other food-approaching behaviors have also been identified, for example, food responsiveness (i.e., the tendency to eat in response to food cues such as sight and smell of food), which is positively associated with emotional eating (Ashcroft et al, 2008;Steinsbekk, Belsky, & Wichstrom, 2016). Eating in response to negative emotions is also one pathway in the etiology of bulimia nervosa and binge eating (Pearson, Riley, Davis, & Smith, 2014;Stice, 2001;Stice, Presnell, & Spangler, 2002). But the origins of emotional eating remain unclear.…”
mentioning
confidence: 99%